Analisis Efektivitas Strategi Odd Pricing Terhadap Purchasing Decision Produk Samsung Melalui Shopee - Febriani, Tika Arizona; Agustin, Viranisa Dwina; Angriani, Ria; Maulina, Vira (Accounting Information System, Taxes and Auditing Journal (AISTA Journal), 2025)
Odd Pricing strategy is an important aspect in product marketing in a competitive market. This study aims to assess how the display of prices with odd numbers affects consumer decisions to purchase goods, especially electronic products in the Shopee marketplace. A quantitative approach is used in this study. Shopee customers who have purchased electronic goods are the research population. While the sample is male/female Shopee users who have purchased Samsung products in the electronics category, and are exposed to the odd pricing strategy in purchasing. A total of 50 data were collected through an online questionnaire. Non-probability sampling is the method used to obtain samples. Data analysis was carried out using SPSS statistics 30.0. The results of the study indicate that (1) the display of odd prices affects consumer purchasing decisions in the Shopee marketplace; (2) odd prices have a 17.8% effect on purchasing decisions for electronic products in the Marketplace; and (3) The odd pricing strategy has an impact on increasing consumer interest and choice to buy Samsung products on Shopee.